Nicotine trails in schools: Smoking behavior among junior high school students in Indonesian tobacco production areas - Afanin Halqim; Eva Imania Eliasa; Fayruziyah Ifroch Sabtana (Privietlab, 2026)
The future of the Indonesian is now seriously threatened by the high incidence of smoking behaviors among Indonesian adolescents. This study aimed to investigate the prevalence and factors associated with smoking behavior among high school students residing in tobacco-producing regions in Indonesia. Students' smoking behaviors, sociodemographic traits, and exposure to tobacco marketing were all gathered through a cross-sectional survey. In order to participate in this study, 210 junior high school students answered questions about their smoking habits. The results showed nearly one in five students reported currently smoking (19%), while 22.9% had experimented with smoking but had already quit. More than half of the students (51.9%) reported having received at least one offer to smoke, suggesting strong social exposure to smoking within their environment. Among students who smoked, the most common motivations were the appealing taste of cigarettes (35%) and the desire to appear cool (23%), while stress relief (33.3%) was the primary reason for continuing the behavior. These results highlight how crucial it is to apply evidence-based tobacco control measures in these areas in order to lower the prevalence of adolescents smoking. The findings have implication for educators and parents to monitor tobacco use and provide assistance in quitting tobacco usage.